Application of ALINEA ramp control algorithm to freeway traffic flow on approaches to Bosphorus strait crossing bridges - Demiral, Caglar; Celikoglu, Hilmi Berk (Elsevier BV, 2011)
AbstractBeginning from the 1960ies sustainability has been being pointed out as an important criterion in development which made many countries plan sustainability originated progressing policies. The decision makers, planning to construct a third roadway bridge to connect Asia and Europe continents on to the Bosphorus in Istanbul metropolitan area, first have to evaluate the exaggerated road traffic congestion phenomenon. Before making such a non-environmentally friend decision, advanced traffic managing strategies have to be incorporated to regularize the current pattern of traffic flows on the existing road network that prevails the road based urban transport.Ramp control is an efficient strategy that has been employed to prevent recurrent traffic congestion since 1970ies. With the employment of ramp control applications, several benefits of ramp management, including i.e., the increase on the level of traffic safety, the increase on travelling speeds and consequently decrease on travelling times, the increase on the level-of-service, increase on energy consumption efficiency, decrease on environmental impacts, and increase on user satisfaction, have been experienced. The present paper aims to impose advanced traffic management schemes, specifically the ramp control, on the non-efficient utilisation of freeway approaches to existing Bosphorus bridges as an alternative to a third bridge crossing.
Keywords: ramp control; sustainibility; traffic management